Detection and molecular characterization of bovine leukemia virus in various regions of Iran. (26th July 2019) - Kazemimanesh, Monireh; Madadgar, Omid; Steinbach, Falko; Choudhury, Bhudipa; Azadmanesh, Kayhan
Abstract : Purpose . Bovine leukemia virus (BLV) infects cattle worldwide, imposing an economic impact on the dairy cattle industry. The purpose of this study was to evaluate the molecular epidemiology of BLV in Iran. Methodology . Blood samples taken from 280 cows aged over 2 years old from 13 provinces of Iran were used for leukocyte count and blocking ELISA. Genomic DNA was extracted from the peripheral blood leukocytes of BLV-infected samples and fetal lamb kidney cells to perform PCR of partial env, rex and tax genes and long-terminal-repeat region. The PCR products were sequenced, the phylogenetic tree of each gene was constructed, and nucleotide and amino acid sequence pair distances were calculated. Results . The frequency of BLV infection was 32.8 % among animals and was 80 % among provinces. In BLV seropositive animals, the rate of persistent lymphocytosis was 36.9 %. The constructed phylogenetic trees showed the presence of two BLV genotypes (1 and 4) in Iranian strains. As previous studies, our results showed that the env gene was more variable than previously thought, the Rex protein could withstand more amino acid changes compared to the Tax protein, and no significant differences were observed in average changes of the nucleotide of these genes between clinical stages. Conclusions . Our data indicates an increase in the frequency of this infection in Iran. This is the first study report of the presence of BLV genotype 4 in Iranian farms. These findings may have an important role in the control and prevention of BLV infection in Iran and other countries.